Posilování konkurenceschopnosti firmy - Svobodová, Ilona (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Tato diplomová práce se zabývá zhodnocením současné situace firmy Geprostav Hodonín v.o.s. v jejím konkurenčním prostředí. Zkoumá konkurenceschopnost firmy na základě analýzy vlivu mikroekonomických a makroekonomických faktorů. Dle zjištěných skutečností je vytvořen návrh, který posílí její konkurenceschopnost do budoucna.

This diploma thesis deals with evaluation of current situation of the Geprostav Hodonín v.o.s. company in its competitive environment. Based on the analysis of microeconomic and macroeconomic aspects, it examines the competitive strength of the company. According to the findings reccommendations to strenghten its competitiveness in the future are suggested.
Increasing the Company’s Competitive Strength
Keywords: Konkurenceschopnost; konkurenční výhoda; strategie; trh; zákazník; Competitiveness; competitive advantage; strategy; market; customer